Notes on the report of the European Law Institute the protection of adults in international situations - Muñoz Fernández, Alberto (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
The European Law Institute (ELI) adopted a Report encouraging the European Union to “Europeanize” a new field of private international law: the protection of adults. The Report provides arguments on the need to take this step, it justifies the EU’s competence to do so and it proposes a double strategy, external and internal. The external one is to authorize the Member States to ratify The Hague Convention on international protection of adults in the interest of the EU and to promote it among third States. The internal action would be the adoption of a Regulation that complements and improves, in the relations between Member States, the functioning of the Convention.